One-step preparation of sulfur-doped porous g-C3N4 for enhanced visible light photocatalytic performance. Issue 24 (11th June 2020) - Xiao, Xin; Wang, Yihui; Bo, Qiu; Xu, Xingyou; Zhang, Dongen
Abstract : Nonmetal doping is a convenient method to adjust the visible light photocatalytic activity of graphitic carbon nitride (g-C3 N4 ). Abstract : Nonmetal doping is a convenient method to adjust the visible light photocatalytic activity of graphitic carbon nitride (g-C3 N4 ). Herein, highly active sulfur-doped porous g-C3 N4 (C3 N4 –S) was successfully prepared by one-step calcination using thiourea and melamine as the precursors. C3 N4 –S exhibited excellent photocatalytic performance for the degradation of Rhodamine B (RhB) under visible light irradiation. C3 N4 –S not only promoted the separation of photogenerated electron–hole pairs, but also enhanced electron transfer, resulting in a great improvement in the photocatalytic efficiency. Based on capture experiments and DMPO spin-trapping ESR spectra, the superoxide radical (˙O2 − ) was proved to be the predominant active species and the possible photocatalytic mechanism of C3 N4 –S was proposed. The photocatalytic mechanism of RhB degradation over C3 N4 –S was further explored using high-resolution mass spectra (HRMS).